2021
DOI: 10.1159/000517233
|View full text |Cite
|
Sign up to set email alerts
|

Regional Citrate Anticoagulation during Double-Filtration Plasmapheresis in Kidney Transplant Recipients: A Single-Center Retrospective Cohort Study

Abstract: <b><i>Introduction:</i></b> Double-filtration plasmapheresis (DFPP) may be used for immunomodulation in kidney transplant (KTx). While DFPP reduces plasma product exposure, risk of circuit clotting merits adequate anticoagulation. Regional citrate anticoagulation (RCA) avoids the risks of systemic anticoagulation, but a protocol for RCA-DFPP is not previously widely described. <b><i>Methods:</i></b> We conducted a single-center retrospective cohort study involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…nontransplant patients and in kidney transplant patients, 11,12 comparative studies with systemic heparin anticoagulation have not been published. This study showed no significant difference in circuit patency between RCA and systemic heparin anticoagulation for DFPP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…nontransplant patients and in kidney transplant patients, 11,12 comparative studies with systemic heparin anticoagulation have not been published. This study showed no significant difference in circuit patency between RCA and systemic heparin anticoagulation for DFPP.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulopathies may occur commonly during DFPP, independent of the choice of anticoagulation technique, which can increase the risk of bleeding. 12,27 Bleeding and use of blood products may be numerically higher in the RCA-DFPP arm since the choice of anticoagulation therapy was at the discretion of treating physicians, and RCA-DFPP was more likely to be selected for patients with a higher risk of bleeding and coagulopathy. In patients with coagulopathy or at higher risk of bleeding, blood products such as cryoprecipitate may have been more frequently used to offset the effect of DFPP and prevent active bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations